Identifikasi Korban Bencana Massal: Praktik DVI Antara Teori dan Kenyataan - -, Henky; Safitry, Oktavinda (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 2 (2012): Indonesian Journal of Legal and Forensic Sciences)
The role of forensic pathologist in mass disaster is to identify the dead victims. Identification procedure refers tothe DVI (Disaster Victim Identification) Interpol guideline. DVI process consists of 5 phases, The Scene, PostMortem Examination, Ante Mortem Information Retrieval, Reconciliation and Debriefing. Post Mortem (PM)and Ante Mortem (AM) data that are collected include finger prints, dental records and DNA as PrimaryIdentifiers and also medical records and property as a Secondary Identifiers. AM data populated into the yellowform and PM data into a pink form. In the reconciliation phase, someone stated identified, by comparing theAM and PM data. At least there is a match between one Primary Identifiers or two Secondary Identifiers.Theoretically, the five phase of DVI should be done according to DVI standard in every case ofdisaster. In fact, many obstacles and constraints are met in the field to implement the DVI guidelines. A lot ofcorpses, limited number of storages, pathologist and time, family authority, as well as lack of coordination, risemany problems in implementing DVI procedures consistently. This article will discuss the various constraintsand problems that encounters when carrying out DVI guidelines in the case of RIMBA III ship sinking, Herculesplane crash at Magetan and Earthquakes at Padang.
Keywords: identification – mass disaster – DVI